2018
DOI: 10.1111/ggr.12220
|View full text |Cite
|
Sign up to set email alerts
|

Handheld Laser Induced Breakdown Spectroscopy Instrumentation Applied to the Rapid Discrimination between Iron Meteorites and Meteor‐Wrongs

Abstract: Meteorites are rocks that once were part of planets or large asteroids, and usually contain a great amount of extra‐terrestrial iron. Nowadays, the meteorite business is booming and the demand is increasing all over the world, whereas supply (originating especially from Morocco and Algeria) is limited. Thus, specimens presented as meteorites often turn out to be common Earth rocks or old smelter and castoff iron dubbed as a ‘meteor‐wrong’. In the present study, a compact handheld instrument based on fast‐respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Identical to the previous study, the Dergaon meteorite shows depleted K concentration and Na concentrations much larger than K concentrations. It is an inherently K-depleted H+chondrite [2] rather than the previously suggested impact-induced high-temperature alkali devolatilization process [3], since the laser-induced breakdown spectroscopy applied in the present study did not alter the inferred concentrations of alkali elements.The elevated Mg (13.44%wt), Ni (1.30%wt), and Cr (0.55%wt) contents and confirmed presence of Ir (the spectral line at 351.364 nm) analogous to previous studies [2,9,16], and the petrographic observations establish the Dergaon sample as a chondrite meteorite. In addition to the characteristic atomic lines of the elements that were recorded, the spectra also show molecular bands of molecules composed of elements that display relatively higher concentration.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Identical to the previous study, the Dergaon meteorite shows depleted K concentration and Na concentrations much larger than K concentrations. It is an inherently K-depleted H+chondrite [2] rather than the previously suggested impact-induced high-temperature alkali devolatilization process [3], since the laser-induced breakdown spectroscopy applied in the present study did not alter the inferred concentrations of alkali elements.The elevated Mg (13.44%wt), Ni (1.30%wt), and Cr (0.55%wt) contents and confirmed presence of Ir (the spectral line at 351.364 nm) analogous to previous studies [2,9,16], and the petrographic observations establish the Dergaon sample as a chondrite meteorite. In addition to the characteristic atomic lines of the elements that were recorded, the spectra also show molecular bands of molecules composed of elements that display relatively higher concentration.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the wavelengths of spectral lines for characteristic elements found in the Dergaon meteorite included Ni I (338.05, 341.34, 342.37, 349.29 and 352.454 nm), Co I (340.51, 344.364, 347.39and 349.56 nm), and Ir I (351.364 nm). Identical spectral lines of these elements are also observed in meteorites, recently analyzed with LIBS [16]. An earlier study of the Dergaon meteorite reported the presence of noble gases and some light elements as well [2].…”
Section: Speciesmentioning
confidence: 66%
See 1 more Smart Citation
“…With the commercial availability of handheld LIBS instruments utilizing microchip lasers with pulse energies around 6 mJ, and broadband spectrometers covering a spectral range from 190 to 950 nm, geological and environmental applications became possible. In these works, the applicability of the handheld instruments for geochemical fingerprinting [36], calibration curves of Cu and Al alloys [37] and geological discrimination of, e.g., meteors and fakes [38,39] were investigated. Further applications are described in two reviews on portable spectroscopy [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…It is a relatively well studied chondritic meteorite [3][4][5][6][7][8][9][10] possessing some interesting characteristics, such as the potassium-depletion associated with vesiculated feldspar, the presence of aliphatic hydrocarbons [8][9] and nano-diamonds [10] observed using conventional analytical techniques (including Gamma Ray, FTIR and Laser Raman, etc.). Meteorites were successfully analyzed by laser-induced breakdown spectroscopy (LIBS) [11][12][13][14][15][16]. For the quantitative elemental analysis of the meteorite, calibration-free LIBS (CF-LIBS) approach is used to determine the elemental composition of Dergaon meteorite.…”
Section: Introductionmentioning
confidence: 99%